Implementasi Metode Mujadalah Dalam Westernisasi Gen Z (Studi Empiris di Madrasah Aliyah Negeri Kota Pasuruan) - Fadhiya Mardhatila Amini, M. Ma’ruf (Al-Makrifat: jurnal kajian Islam, 2024)
The case study of westernization, or the adoption of western culture by many members of the Z generation and younger generations, undermines this research. As westernization has grown, it has produced a number of tendencies that may have an impact on the morality of students in MAN Pasuruan cities. The dearth of academic excellence and persuasive discourse can be attributed to Generation Z Westernization movement, which has produced a sizable population of followers. The aim of this study is to explain the application of Mujadalah methods in Westernization Generation Z MAN Pasuruan Cities, their effects as they follow the current of Westernization, and the teachers’ remedy.Based on research in the field. In the Westernization Gen Z MAN Pasuruan City, where before the implementation of the method Mujadalah implemented, She’s a teacher Ita Miftakhul Jannah as eye teacher Teaching Sciences Fikih prepared and formed two groups of the number of students 33, and after being divided into two groups, she distinguished with the group A and Group B, in order to distinguish between those who are interested in Westernization and who are not interested in westernization. After being divided into two groups and the implementation of the method of mujadalah by She’s a teacher Ita Miftakhul Jannah was given the theme of westernization, the fashion or style of clothing and the application of stickers that contain content from western culture. After the preparation that was presented by the source of She’s a teacher Ita Miftakhul Jannah, then the Implementation of Method of Mujahadalah was carried out in the XD class accompanied by My Mother H who consisted of 33 students who were divided in two groups, group A and group B with themes of Westernization or Western culture has gone as desired, but its implementation has supportive and inhibitory factors. The supporting factor of implementing your method is 1) Students are able to master the topic 2) Quick response when answering. And inhibiting factors in the implementation of the method Mujadalah the 1) Students lack confidence in the course of discussions or methods Mujadalah 2) Students use mixed or non-standard languages 3) Lack of preparation. And the evaluation or outcome of the Method Implementation Mujadalah that is, group A could not respond to group B suggestions well because group B had already explained the facts related to the very bad impact of the current Western media or such westernization. And the impact of westernization is that it can increase friendship, change behavior, access to learning and information, tends to like Western songs, can’t get away from gadgets, accesses pornographic content, plays games without knowing time, speaks in negative-connoted languages. And the solution related to the impact of westernization gen z MAN Pasuruan cities that is teachers have to take a persuasive approach, do practices, teachers must be ushu or example and teachers should be able to collaborate with other teachers regarding cases made by students because of the effects of such westernisation Keywords: Implementation of the Mujadalah Method, Westernization, Gen Z